Effect of clindamycin on the ability of a continuous culture of colonic bacteria to ferment carbohydrate. Issue 4 (April 1986) - Edwards, C A; Duerden, B I; Read, N W
Abstract : A continuous culture model of the proximal colon was used to study the effect of clindamycin on the ability of colonic bacteria to ferment carbohydrate. Six steady state anaerobic cultures of human faeces, in a medium simulating ileostomy effluent, were treated with 26 micrograms/ml clindamycin. They were paired with six untreated cultures, run under identical conditions. Clindamycin treatment eliminated the anaerobic bacteria, significantly decreased osmolality and the output of volatile fatty acids, particularly propionic acid and increased the residual carbohydrate concentration. Doubling the amount of carbohydrate in the medium increased osmolality and the production of volatile fatty acid, though the response of clindamycin treated cultures was less than that of untreated cultures. Attempts to introduce Clostridium difficile into three pairs of cultures were successful in only two cultures after administration with clindamycin and when a heavy inoculum (10(6)-10(9) organisms) had been used.